Recent developments in government debt management: an overview - Williams, Mike (Henry Stewart Talks, 2009)
What is debt management and why it is important, Recent history and current trends |The macroeconomic environment, The building blocks of sound practice in debt management, Debt management objectives, Transparency and accountability, Institutional framework, Debt management strategy, Risk management framework |Developing the government securities market, Issues arising in developed and in emerging market countries